Australian Cattle Dogs with Neuronal Ceroid Lipofuscinosis are Homozygous for a CLN5 Nonsense Mutation Previously Identified in Border Collies. (20th May 2016) - Kolicheski, A.; Johnson, G.S.; O'Brien, D.P.; Mhlanga‐Mutangadura, T.; Gilliam, D.; Guo, J.; Anderson‐Sieg, T.D.; Schnabel, R.D.; Taylor, J.F.; Lebowitz, A.; Swanson, B.; Hicks, D.; et al.
Abstract : Background: Neuronal ceroid lipofuscinosis (NCL), a fatal neurodegenerative disease, has been diagnosed in young adult Australian Cattle Dogs. Objective: Characterize the Australian Cattle Dog form of NCL and determine its molecular genetic cause. Animals: Tissues from 4 Australian Cattle Dogs with NCL‐like signs and buccal swabs from both parents of a fifth affected breed member. Archived DNA samples from 712 individual dogs were genotyped. Methods: Tissues were examined by fluorescence, electron, and immunohistochemical microscopy. A whole‐genome sequence was generated for 1 affected dog. A TaqMan allelic discrimination assay was used for genotyping. Results: The accumulation of autofluorescent cytoplasmic storage material with characteristic ultrastructure in tissues from the 4 affected dogs supported a diagnosis of NCL. The whole‐genome sequence contained a homozygous nonsense mutation: CLN5:c.619C>T . All 4 DNA samples from clinically affected dogs tested homozygous for the variant allele. Both parents of the fifth affected dog were heterozygotes. Archived DNA samples from 346 Australian Cattle Dogs, 188 Border Collies, and 177 dogs of other breeds were homozygous for the reference allele. One archived Australian Cattle Dog sample was from a heterozygote. Conclusions and Clinical Importance: The homozygous CLN5 nonsense is almost certainly causal because the same mutation previously had been reported to cause a similar form of NCL in Border Collies. Identification of the molecular genetic cause of Australian Cattle Dog NCL will allow the use of DNA tests to confirm the diagnosis of NCL in this breed.